A Multi-Criteria Decision-Making Methodology for Improving the Supply Chain Management: Aviation Fuels Case Study - AbdelAziz, Nabil M.; Mohamed, Dina; Soliman, Hasnaa (International Journal of Computers and Informatics (Zagazig University), 2025)
A supply chain is a framework that involves everything to originate and sell a product or service. A sustainable supply chain encompasses environmentally and socially sustainable activities on all parts of the chain and bolsters environmental and social standards to reduce greenhouse gas releases and environmental decay. The aviation area is one of the biggest participants in greenhouse gas releases. Today, the world is moving to protect the climate and reduce emissions of harmful fuels. This is why industrial areas, including the aviation area, are searching for sustainable fuels that reduce emissions, preserve the climate, and limit increasing environmental decay. The aim of this study is to pick out the most sustainable substitute aviation fuel via a multi-criteria decision-making (MCDM) based evaluation model. This model combined criteria importance through inter-criteria correlation (CRITIC) and the stable preference ordering towards ideal solution (SPOTIS) methods. The CRITIC method is applied to compute the weights of the criteria. The SPOTIS methodology is applied to rank the substitutes. This study evaluates four substitute aviation fuels against twenty criteria. According to the preferences of six aviation experts, we showed that Algae-fuel is the best and Soybean-fuel is the worst. To demonstrate the suggested method’s resilience, we contrast it with alternative approaches. The purpose of the sensitivity analysis was to demonstrate the rank’s reliability under various scenarios.